2014
DOI: 10.1016/j.gynor.2013.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Desmoplastic small round cell tumor of the ovary: A rare but devastating disease in young women

Abstract: HighlightsDesmoplastic small round cell tumor of the ovary is a rare clinical entity with poor prognosis.Accurate diagnosis utilizes a combination of histological, immunohistological, and cytogenetic findings.This disease should be kept on the differential diagnosis in young women with widespread disease on presentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 10 publications
(13 reference statements)
0
15
0
Order By: Relevance
“…Only 15 cases previously reported in women in the English literature (3). A summary of the 15 cases is presented in Table II ( [2][3][4][5][6][7][8][9][10]. Compared with the present case with the reported cases in Table II, the majority of the characteristics of the present case were similar to the others, including the locations, which were unilateral or bilateral ovarian involved and presented as solid and/or cystic.…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations
“…Only 15 cases previously reported in women in the English literature (3). A summary of the 15 cases is presented in Table II ( [2][3][4][5][6][7][8][9][10]. Compared with the present case with the reported cases in Table II, the majority of the characteristics of the present case were similar to the others, including the locations, which were unilateral or bilateral ovarian involved and presented as solid and/or cystic.…”
Section: Discussionmentioning
confidence: 50%
“…The patient in the present study was slightly older than this mean at 31 years old. Only 15 cases previously reported in women in the English literature (3). A summary of the 15 cases is presented in Table II ( [2][3][4][5][6][7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hattori et al suggested that prominent cytoplasmic vacuoles and cohesion in serous effusions of DSRCT may resemble metastatic adenocarcinoma [7]. DSRCT occurs rarely in females and can masquerade ovarian cancer [8]. Zeeshanud-din et al reported two cases of intra-abdominal desmoplastic small cell tumour resembling adenocarcinoma of colon [9].…”
Section: Clinical History and Examinationmentioning
confidence: 99%